KINE[SIS]TEM’17 From Nature to Architectural Matter International Conference - Oliveira, M. J.; Rato, V.; Leitão, C. (Nexus Network Journal, 2018)
With nature as a starting point, KINESISTEM’17 was the first International Conference held in Portugal aiming to share and debate research and design work related to the integration of natural geometries, mechanics and systems fundamentals applied to the scale, function and aesthetics of architecture. Four prominent guest keynote speakers set the pace of the conference: Manuel Kretzer, Alex Haw, Bob Sheil and Alberto Estévez. Gathering academics, students and designers, a significant set of research and practice works was presented and the interplay between diverse scientific fields was also a strong feature at the conference, with attendants coming from areas such as architecture, design, electronics, mechanics, computer science, biology and sociology. This report summarizes the KINE[SIS]TEM’17–From Nature to Architectural Matter International Conference hosted by ISCTE-Instituto Universitário de Lisboa in June 19th–20th, 2017.